Coefficients Bounds for Certain Subclass of Biunivalent Functions Associated with Ruscheweyh q-Differential Operator. (5th September 2017) - Hussain, Saqib; Khan, Shahid; Zaighum, Muhammad Asad; Darus, Maslina; Shareef, Zahid
Abstract : We introduce in our present investigation a new subclass of analytic and biunivalent functions associated with Ruscheweyh q -differential operator in open unit disk E . We use the Faber polynomial expansions to find n th coefficients bounds of class of bisubordinate functions and also find initial coefficient estimates.